Pb (II) Recovery by Modified Tuffite: Adsorption, Desorption, and Kinetic Study - Beyhan Kocadagistan; Kubra Oksuz (Adsorption Science & Technology)
In this study, Pb (II) removal from wastewater was investigated using a modified vitric crystal tuffite with a BET surface area of 11.7 m2/g. For this purpose, tuffite was used in its natural and modified form with ethylenediaminetetraacetic acid (EDTA). Batch adsorption experiment was performed. The effects of contact time (0–90 min), adsorbent dosage (1–10 g/L), initial concentration (10–200 mg/L), and pH (2–12) on the removal of Pb (II) were investigated. The isotherm data were fitted to Langmuir, Freundlich, Temkin, and Redlich-Peterson isotherm models. Kinetic models such as pseudo-first-order, pseudo-second-order, and intraparticle diffusion models were used. In order to optimize the adsorption system and investigate the kinetic behaviour of adsorption, nonlinear isotherm and kinetic models were used as well as linearized models. Error analyses were made in order to express the obtained results more accurately. pH 5 was the optimum value for adsorption. According to nonlinear isotherm model calculations, Bayburt stone (BS) and its modified form (MBS) had qmax values of 335 and 584 mg/g, respectively. The Freundlich model, with its high correlation coefficients of about 1.00, was found to be more suitable for the adsorption of Pb (II) to MBS. The pseudo-second-order kinetic model with mean R2 and k2 values of 0.997 and 0.0116 1/min, respectively, was found to be more appropriate. According to the regeneration studies, the maximum desorption efficiency was 97.8%. The thermodynamic equilibrium coefficients obtained at different temperatures and ΔGo, ΔHo, and ΔSo values were observed as -21.4, 46.4, and 163 kJ/mol, respectively. These values indicate that the adsorption of Pb (II) on to MBS was endothermic and spontaneous process. BS and MBS were characterized by different instrumental analyses such as SEM, EDS, FTIR, and zeta potential measurements.